Peran Kepolisian Dalam Menangani Tindak Pidana Pencabulan Anak Di Polres Nias - Yoseph Andrian Meitianus Lase (Iuris Studia: Jurnal Kajian Hukum, 2022)
Children are creatures of God Almighty who have human rights like other human beings, so that no human or other party can rob them of these rights. Children have a strategic role and the state guarantees the rights of every child to survival, growth and development as well as protection from violence and discrimination. Problems related to children often occur in Indonesia, for example regarding sexual abuse of children, including within the jurisdiction of the Nias Police Station. The factors that cause sexual abuse by children based on interviews with researchers with the Nias Resort Police PPA are: gender factors, family factors, education factors, environmental factors, alcoholic beverages and technology factors. one of the functions of state government in the field of maintaining public security and order, law enforcement, protection, shelter, and service to the community. The role of the Police is to realize internal security which includes the maintenance of public security and order, orderly and law enforcement, the implementation of protection, protection, and public service, as well as the creation of public peace by upholding human rights. Efforts that can be taken in overcoming the crime of obscene acts are criminal policies or crime prevention policies, one of which can be taken through a penal policy, namely law enforcement by punishing the perpetrators of crimes. Non-penal efforts to overcome the crime of sexual abuse of minors are carried out through legal counseling to the community regarding the importance of preventing children from becoming victims of sexual abuse and efforts to obtain legal certainty if children become victims.